The Influence of Comic Media on the Learning Motivation of Fourth-Grade Students at SDN Guyung 2 in the Material on the Arrival of Foreign Nations in Indonesia - Hastuti, Dian Nur Antika Eky; Arifah, Tsania Fadilla (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to determine the influence of using comic media on the learning motivation of sixth-grade students at SDN Guyung 02, Gerih Subdistrict, Ngawi Regency. The research subjects consisted of 27 students. The type of research used is quantitative with an ex-post facto correlation design. Data collection was conducted through observation, questionnaires, and documentation. Based on the hypothesis testing results, a significance level of 0.000 0.05 was obtained, indicating that the use of comic media has an influence on the learning motivation of sixth-grade students at SDN Guyung 2, Gerih Subdistrict, Ngawi Regency. Therefore, it can be concluded that students taught using comic media exhibit better learning motivation compared to those not taught using comic media.